ANALISIS HUKUM TENTANG PENDAFTARAN TANAH ULAYAT YANG MENJADI HAK PERORANGAN PADA TANAH ULAYAT DI KABUPATEN DAIRI - LAMHOT HERIANTO SIGIRO (PREMISE LAW JURNAL, 2016)
As an adat community, the majority of people in Parbuluan Subdistrict comply with Batak adat law. Each plot of land in Batak community is controlled by certain marga (clan) as the owner of village adat land. Since law No. 5/1960 on Basic Agrarian Regulations is in effect, land registrations becomes the most important thing in the land system in Indonesia because it is the beginning of the process of the bird of land rights ownership. The adat law community in Parbuluan Subdistrict who wants to register their land has to request for Raja Huta/Kepala Huta (village head) by submitting an amount of money which is called “Tulak Sakkul” as a token that the marga land rights has been released and is allowed to be registered for getting its certificate. “Tulak Sakkul” is submitted in an adat ceremony by having meal together as a proof that the village land owner, represented by the village head, has submitted his rights on the marga land. Keywords: Land registration, Marga Land, Parbuluan Subdistrict